A Case of Acute Gastric Mucosal Lesion and Acute Perforated Necrotic Cholecystitis that combined Portal Venous Gas - Yoshida, Ryuuichi; Matsumoto, Hiroshi; Mitsui, Kazuhiro; Namiki, Kenji; Kokaguchi, Kyosuke; Takahashi, Takehiro; Konno, Fumihiro (Nippon Shokaki Geka Gakkai zasshi, 2007)
A 87-year-old man seen in an emergency for sudden onset upper right quadrant pain, coffee-ground vomiting and a medical history of hypertension was found to have tenderness and muscle guarding in the upper right quadrant. Laboratory data showed WBC 23, 700/μl, CRP 22.28mg/dl, and severe inflammation. Plain abdominal X-ray showed marked gastric dilation. Abdominal computed tomography showed widespread hepatic portal venous gas in the liver and portal venous gas in the gastric border vein, splenic vein, and superior mesenteric vein, and gas imaging in the gastric wall. The gallbladder was distended and edematous and showed fluid collection around the gallbladder. We conducted emergency laparoscopic exploration for gastrointestinal necrosis or possible acute cholecystitis, then laparoscopic cholecystectomy under an intraoperative diagnosis of acute perforated necrotic cholecystitis. Postoperative gastroduodenal endoscopy showed multiple erosions with an ulcer in the gastric subcardia and antrum of the stomach. The man was definitively diagnosed with acute perforated necrotic cholecystitis combining broad portal venous gas due to an acute gastric mucosal lesion and gastric dilation and discharged on postoperative day 16.